2017
DOI: 10.1126/scitranslmed.aah6733
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of prefrontal cortex excitation/inhibition balance rescues social behavior in CNTNAP2 -deficient mice

Abstract: Alterations in the balance between neuronal excitation and inhibition (E:I balance) have been implicated in the neural circuit activity–based processes that contribute to autism phenotypes. We investigated whether acutely reducing E:I balance in mouse brain could correct deficits in social behavior. We used mice lacking the CNTNAP2 gene, which has been implicated in autism, and achieved a temporally precise reduction in E:I balance in the medial prefrontal cortex (mPFC) either by optogenetically increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
236
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(263 citation statements)
references
References 46 publications
24
236
3
Order By: Relevance
“…Previous work has also linked mPFC E/I balance disruption to impairments in sociability (52, 55), and consistent with this, we found that social preference, which was disrupted by MD inhibition, was also ameliorated by increasing PVI activity. We determined that these disruptions in sociability were not due to increased anxiety in the affected groups, given that both groups with social interaction deficits exhibited an anxiolytic phenotype on the EPM.…”
Section: Resultssupporting
confidence: 90%
“…Previous work has also linked mPFC E/I balance disruption to impairments in sociability (52, 55), and consistent with this, we found that social preference, which was disrupted by MD inhibition, was also ameliorated by increasing PVI activity. We determined that these disruptions in sociability were not due to increased anxiety in the affected groups, given that both groups with social interaction deficits exhibited an anxiolytic phenotype on the EPM.…”
Section: Resultssupporting
confidence: 90%
“…Social interactions involve a circuit of brain structures that includes PFC, hippocampus, amygdala, or other cortical areas susceptible to be altered in ASD. The E-I balance of the PFC is important for both normal and pathologic social interactions (75,76), and we demonstrate here that both social interactions and the E-I balance of the PFC are dysfunctional in the absence of CD38. Our results in juvenile male mice indicate that a decrease in USV emission rate (77) preceded the social alterations seen in adults.…”
Section: Discussionsupporting
confidence: 55%
“…Of note, alterations in inhibitory network activity can lead to an imbalance between excitatory and inhibitory currents (E/I balance), a mechanism that likely underlies ASD (Nelson & Valakh, 2015). In this regard, the reduction of the E/I balance in Cntnap2 KO mice was able to acutely rescue their hyperactivity and deficits in social behavior (Selimbeyoglu et al, 2017).…”
Section: Pathological Modelsmentioning
confidence: 99%